Tasty but Nasty? The Moderating Effect of Message Appeals on Food Neophilia/Neophobia as a Personality Trait: A Case Study of Pig Blood Cake and Meatballs - Yen-Cheng Chen; Ching-Sung Lee; Shuo-Hui Kuan (Foods, 2021)
Given the development of food tourism, food culture has become an important motivation for tourists. This study focuses on food tourism and examines the effects of message appeal and personality traits (food neophilia or neophobia) on tourists’ willingness to consume pig blood cake (PBC) and meatballs, two rice-based Taiwanese street foods. A total of 181 valid questionnaires were administered to foreign tourists in Taiwan (the majority of subjects were Europeans and Americans) through snowball sampling. The questionnaires were analysed using the AMOS 6.0 statistical software package. Foreign tourists’ food neophobia or neophilia was found to significantly affect their willingness to consume rice-based Taiwanese street food (PBC and meatballs) and to strongly regulate the effect of message appeal on their willingness to consume the two delicacies. Past studies on food neophobia/neophilia traits have mostly focused on Western and European foods and have rarely investigated the effect of message appeal on the consumption of traditional rice-based street food in Eastern Asia (e.g., Taiwanese special delicacies). This study’s most important contribution is that food neophilia or neophobia moderates the message appeal effect on foreign tourists’ intention to consume local delicacies. This finding has implications for the hospitality industry and relevant government agencies in Asia for the marketing and promotion of food tourism.